Morphological Characteristics of Aortal Endothelium in Rats With Chronic Renal Insufficiency Following Injection of Rat Placental Cryoextract, Application of RAAS Medicated Blockade and Their Combined Action - Chizh, Yuliia; Repin, Mykola; Marchenko, Larisa; Strona, Vera; Govorukha, Tatyana (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 286